Omalizumab as alternative to chronic use of oral corticosteroids in severe asthma. (April 2019) - Katsaounou, Paraskevi; Buhl, Roland; Brusselle, Guy; Pfister, Pascal; Martínez, Rafael; Wahn, Ulrich; Bousquet, Jean
Abstract: Systemic/oral corticosteroids (OCS) have been used for decades in the management of acute asthma exacerbations and chronically in patients with uncontrolled severe asthma. However, while OCS are effective at treating acute exacerbations, there is only empirical evidence regarding the efficacy of OCS at reducing the rate of exacerbations. Evidence, although scarce, is suggestive of high exacerbation rates in severe asthma patients even when receiving maintenance treatment with OCS. In addition, use of OCS is associated with undesirable effects. Despite all this, physicians have continued to use OCS for managing severe asthma and acute exacerbation due to the lack of availability of effective alternatives. Fortunately, in the last decade several biologics have been proven safe and effective for patients with uncontrolled severe asthma. This has led to the Global Initiative for Asthma (GINA) recommending the use of biologics, instead of maintenance OCS, in patients with severe asthma (GINA Step 5). These include one biologic targeting immunoglobulin E (IgE) (omalizumab), and different biologics targeting interleukin-5 (IL-5), the IL-5 receptor (IL-5R) or IL-4 receptor α-unit (IL-4R α), including mepolizumab (subcutaneous), reslizumab (intravenous), benralizumab (subcutaneous) and dupilumab (subcutaneous). Omalizumab for the treatment of severe allergic asthma reduces exacerbations, irrespective of blood eosinophil levels. Anti-IL-5/IL-5R biologics are indicated in patients with severe eosinophilic asthma and repetitive exacerbations, irrespective of the presence or absence of allergy. Recently, an anti-IL4Rα biologic has been approved by the FDA for eosinophilic phenotype or oral corticosteroid-dependent asthma. Finally, physicians should consider using biologics as an alternative to chronic OCS therapy. Highlights: Oral corticosteroids (OCS) are associated with several adverse effects. OCS should be prescribed to patients after careful assessments of potential risks compared to benefits. Omalizumab has 15 years of clinical experience with more than 800, 000 patient-years of exposure which make it the first choice of add-on therapy in patients with severe allergic asthma. Biologics such as omalizumab (anti-immunoglobulin-E) or anti-interleukin (IL), IL-5 and IL-4/IL13, targeting biologics should be considered as alternatives to OCS in patients with uncontrolled severe asthma. Physicians should either prescribe the appropriate biologic therapy or refer patients with corticosteroid-dependent severe asthma to a specialist.